2021
DOI: 10.3390/ma14123330
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Resistive Switching Performance in Sulfur-Doped HfOx-Based RRAM

Abstract: In order to improve the electrical performance of resistive random access memory (RRAM), sulfur (S)-doping technology for HfOx-based RRAM is systematically investigated in this paper. HfOx films with different S-doping contents are achieved by atmospheric pressure chemical vapor deposition (APCVD) under a series of preparation temperatures. The effect of S on crystallinity, surface topography, element composition of HfOx thin films and resistive switching (RS) performance of HfOx-based devices are discussed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The obtained discrete coefficient ( SD /mean) for set and reset state are 0.37 and 0.97 respectively. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained discrete coefficient ( SD /mean) for set and reset state are 0.37 and 0.97 respectively. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…The obtained discrete coefficient (SD/mean) for set and reset state are 0.37 and 0.97 respectively. [42] Table 1 summarizes the different materials, exhibiting write once read many (WORM) characteristics with analog switching together with characteristics of the present device. It seems that most of the devices exhibit good retention time and high endurance cycles.…”
Section: Resultsmentioning
confidence: 99%
“…25 Another previous study reported that oxygen vacancies (V o ) can be added to HfO x through S doping resulting in device improvement such as more uniformity in resistance change and stable endurance. 26 In addition, an increase of oxygen vacancy (V o ) defect concentration in the active layer has been shown to lead to enhanced switching characteristics such as stable multi-level resistive switching, a higher on/off ratio, and gradual reset behvaior. 27 Al-Doped HfO x based devices along with post-deposition annealing have been shown to have promising multi-level switching characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to optimize to improve analog RS is doping. Ti [3], Al [4,5], Mg [6], Ni [7], Au [8], S [9] have been introduced as dopants into HfO 2 layers to tailor the formation of CFs, resulting in improved RS performance and gradual switching. On the other hand, the metal/oxide interface is significant for the formation and dynamics of V O and thus many efforts have been carried out to engineer the interfaces to optimize the multilevel RS and the reliability.…”
Section: Introductionmentioning
confidence: 99%